Supply Chain Management System Model in Digital for Electric Power Management in Thailand - Artaphon Chansamut (ExcelingTech, 2022)
The article was conducted to study and evaluate supply chain management system model in digital for electric Power management in Thailand. The samples in the research study consisted of ten purposively selected experts consisted of five experts on supply chain management, five experts on Digital Technology, Data were analysed by arithmetic mean and standard deviation. The research findings model ten elements namely main components, Suppliers, Power plant generates electricity, Substation, Transmission, Substation, Power Lines satisfaction, Return and consumers. The assessment supply chain management system model in digital for electric Power management in Thailand using Black-Box technique and The results from experts agreement supply chain management system model in digital for electric Power management in Thailand was a high level and can be appropriately applied in actual work settings.Â